Systemic delivery of free chitosan accelerates femur fracture healing in rats - Shao, P.; Wei, Y.; Dass, Crispin; Zhang, G.; Wu, Z. (2018)
© 2018 Bentham Science Publishers. Background: Chitosan-containing compounds have been shown to be suitable for bone replacement, but few studies demonstrate the impact of the chitosan as a free drug on the fracture.In this study, we aimed to evaluate possible effects of free chitosan on fracture healing. Materials and Methods: Thirty adult male Sprague-Dawley rats with a mean body weight of 205 g (range from 200g to 210g) were randomly and equally divided into two groups. Standardized femur fractures were created in all rats. Treatments were administered intraperitoneally twice weekly at 1 mg chitosan per injection and the controls were administered physiological saline. The site of the fracture was compared with the control group at 1, 2 and 4 weeks after surgery (n=5 in each group). The weight, activity and reaction of the rats were observed at all the timepoints. Anterior-posterior radiographs and micro-CT scans of all fractures were taken after surgery, and the parameters included: the volume of callus that was calculated using the Perkins volume formula, BV/TV, BV, BMD of cortical bone, cortical thickness, and cortical number at the fracture sites. After sacrifice, fractured femurs from rats were dissected and carefully cleaned of muscle around the fracture callus to preserve callus integrity. Sections were stained with haematoxylin and eosin for histological evaluation of healing. Result: Radiological (X-ray and micro-CT) evaluation showed that fracture healing of the experimental group was better than control group at the second week and fourth week. Histological evaluation revealed fracture healing of the experimental group was better than control group at the same time. There was no statistically significant difference in fracture healing between the two groups at the first week. Conclusion: Systemic delivery of free chitosan can accelerate the bone healing process in rat femur fracture at the early-middle stage.